The Effectiveness of Peppermint Aromatherapy on Physiological and Emotional Arousal in Preoperative Patients - Muhlisoh; Hasaini, Asni; Sukmawaty, Martini Nur (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2025)
Surgical procedures often pose significant physiological and psychological stress for patients. The number of surgical cases continues to increase annually. This study aimed to analyze the effectiveness of peppermint aromatherapy in reducing physiological and emotional arousal among preoperative patients. A quasi-experimental design with a pretest-posttest control group was employed, involving 20 respondents at Ratu Zalecha General Hospital Martapura. The results showed significant differences in blood pressure and pulse rate before and after the administration of aromatherapy (p < 0.05), although no significant difference was found between the intervention and control groups. The study concluded that peppermint aromatherapy did not produce a significant effect when comparing the intervention group with the control group. Therefore, future studies with stronger methodological control and more precise timing are recommended.